1272 ОНЫ НУР АД-ДИНИЙ БИЧГИЙН ЗАРИМ ОНЦЛОГ - М.Ууганбаяр, (Acta Mongolica, 2011)
In this brief article author discusses on some peculiarities the vakfiye or letter of Nur el-Din bin Cacaoglu. Cacaoglu the emir of Kirsehir in Anatolia in the time of ruling Mongolian IIkhanidian state had left vakfiye or the letter of foundation on his estates and properties in Arabic and Mongolian. Mongolian part of this letter, which had written in 1272 is a monument of the preclassic written Mongolian. As one of the preclassic written Mongolian monument, in the letter of Nur el-Din occur several words and expressions that from the aspects of writings and meanings might be interesting. For example, Mongolian complex word jige kobegun in this letter no means ‘nephews and sons’ as precedent scholars had considered but only ‘nephews and children’. In Mongolian word kobegun and in Turkish word ogul mean ‘child or kid’. On this occasion, in Mongolian and Turkish we encounter many facts such as ‘oki kobun, nugun kobun, kiz oglin, uri oglin.